UNDERSTANDING ONLINE TICKET PURCHASE DECISIONS IN FULL-SERVICE AIRLINES: THE INFLUENCE OF SOCIAL MEDIA PROMOTION, BRAND EQUITY WITH E-WOM AS A MEDIATOR - Octaviani, Reni Dian; Dinar, Rexatyo Waskito; Sholihah, Izzatush; Marie, Andhalia Liza; Mege, Stacia Reviany (International Conference on Vocational Business, Logistic, Accounting, Supply Chain, Tax (ICoBLAST); Vol 1, No 1 (2026): 1st ICoBLAST, 2026)
Introduction/Main Objectives: The rise of digital marketing has reshaped how airlines engage with consumers, particularly through social media promotions. The digital promotion, including Electronic Word of Mouth (eWoM), has become a vital element in shaping customer behavior. It refers to online interactions such as reviews, recommendations, and comments that influence customers’ perceptions and decisions when purchasing airline tickets. Background Problems: This research explores whether social media promotion and brand equity enhance consumer trust and how electronic word of mouth influences purchase decision.  Previous studies have focused on the services on low-cost carrier or tourism in general, resulting in a research gap in the context of full-service airlines that put emphasize on customers’ loyalty and quality. Research Methods: Using a quantitative approach, data is collected by surveys of airline passengers who have interacted with social media promotions. Structural Equation Modelling (SEM) is applied to analyze relationships among the variables. Findings/Results: The study found that e-WOM (passengers reviews and online recommendations) did not have a significant influence on online tickets purchases. Conclusion: The findings will help airlines refine digital marketing strategies, strengthen brand perception, and leverage word of mouth marketing to boost customer acquisition Implementation Potential : This study is intended to understand consumer behavior in the airline industry, giving insights for increasing online ticket sales.   Keywords : Social Media Promotion; Brand Equity; Electronic Word of Mouth; Online Ticket Purchase; Consumer Behavior; Full-Service Carriers. JEL Classification: M2